2018
DOI: 10.1016/j.ymeth.2018.01.021
|View full text |Cite
|
Sign up to set email alerts
|

A reconstitution method for integral membrane proteins in hybrid lipid-polymer vesicles for enhanced functional durability

Abstract: Hybrid vesicles composed of lipids and block copolymers hold promise for increasing liposome stability and providing a stable environment for membrane proteins. Recently we reported the successful functional reconstitution of the integral membrane protein cytochrome bo (ubiquinol oxidase) into hybrid vesicles composed of a blend of phospholipids and a block copolymer (PBd-PEO). We demonstrated that these novel membrane environments stabilise the enzymes' activity, prolonging their functional lifetime [Chem. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 42 publications
4
49
0
Order By: Relevance
“…It was expected that the polymeric vesicles would be more resistant to heat exposure as polymer membranes are believed to be more robust than those formed by lipids alone. Polymersomes with a large membrane thickness (PEE 37 -PEO 40 and PBd 46 -PEO 26 ) have previously been shown to have both encapsulation and colloidal stability to autoclave conditions, although there is a slight shift to a smaller vesicle size distribution [28]. To enhance the stability of the vesicles during heat sterilisation, it has been suggested that sugars or polyols could be used to stabilise the vesicles [52] and the drug could be encapsulated after vesicles have been autoclaved [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was expected that the polymeric vesicles would be more resistant to heat exposure as polymer membranes are believed to be more robust than those formed by lipids alone. Polymersomes with a large membrane thickness (PEE 37 -PEO 40 and PBd 46 -PEO 26 ) have previously been shown to have both encapsulation and colloidal stability to autoclave conditions, although there is a slight shift to a smaller vesicle size distribution [28]. To enhance the stability of the vesicles during heat sterilisation, it has been suggested that sugars or polyols could be used to stabilise the vesicles [52] and the drug could be encapsulated after vesicles have been autoclaved [38].…”
Section: Discussionmentioning
confidence: 99%
“…Liposomes, composed of natural lipids, form bilayer membranes that closely mimic the structural matrix of native biomembranes. This makes them highly biocompatible and provides a native-like environment if integral membrane proteins are desired to add functionality to the membrane [23][24][25][26][27]. However, deformations, but weak under stretching deformations, with a lysis strain of less than 5% [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…A future study could investigate this phenomenon. It will be also interesting to apply our methodology to lipid/polymer hybrid systems and their use as platform for membrane proteins as the combined properties in terms of stability and biocompatibility would be beneficial [50][51][52][53] . Most importantly, the potential optimization has been shown to yield functional proteovesicles composed of the lipid DOPC or an ABA block copolymer.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid-phospholipid blended membranes display increased stabilityb ut still maintain permeability for small (charged) solutes. [50] To day's biological membranes are mostlyc omposed of lipids, in which proteins are embedded. [47] Well-sealed, stable membranes can also be formed from block copolymers, [48] but the functional incorporation of integral membranep roteins is challenging, especially when the proteins requirespecific lipids as cofactors.…”
Section: Building Blocks For Membranesmentioning
confidence: 99%